AL-WEFAQ Car Rental Reservation System: Car Reservation System - Sheikh Ahmed, Ahmed Mukhtar; Mohd Yunus, Mohd Amin (Applied Information Technology And Computer Science, 2023)
The advancement of technology has had a significant impact on the development of various industries. However traditional car rental businesses often do not advertise their vehicles online, making it difficult for customers to locate and reserve vehicles. This creates a need for a comprehensive platform that can facilitate the car rental process for both businesses and customers. Such a platform would enable car rental businesses to promote their vehicles and increase their visibility to potential customers. Additionally, customers would have access to a wide range of vehicles available for rent, without the need to waste time searching for a suitable car. The goal of this project is to enhance the efficiency and ease of the car rental system by providing an intuitive, user-friendly platform for both admin and customers. This project is a website for a car rental company that allows customers to view available cars, register, see their profiles, and book cars online. In order to book a car, the user must first log in to the system. From there, they can easily search for and reserve cars by providing information such as booking dates and messages. The website displays all relevant car information, including features and an overview, and allows users to write testimonials and modify their profiles and passwords at any time. Admins can add and manage car brands, cars, bookings, testimonials, and pages, among other things. The website is designed to be user-friendly, with a simple layout that is easy to understand, use, and navigate. Overall, it aims to make the process of car rental convenient and straightforward for its users.